FAKTOR KONTRIBUTOR MATURITAS BUDAYA KESELAMATAN PASIEN DI RS KARIADI SEMARANG - Silalahi, Verarica; Sulistyowati, Elyana Sri (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
This study aims to see the contributing factors to the maturity of patient safety culture. This study is a cross-sectional study utilizing secondary data from the results of the 2022-2024 patient safety culture survey totaling 3,892 samples. The results of the study found that the dimensions of staffing and work speed (p=0.026; r=0.038), the dimensions of response to errors (p=0.000; r=0.068), the dimensions of supervisors, managers or clinical leaders supporting patient safety (p=0.037; r=0.025), the dimensions of communication about errors (p=0.000; r=0.077), the dimensions of openness of communication (p=0.000; r=0.080), the dimensions of reporting safety incidents (p=0.001; r=0.055), the dimensions of hospital management support for patient safety (p=0.000; r=0.053), and the dimensions of handover and exchange (p=0.000; r=0.073) were related to the maturity of patient safety culture, while the dimensions of teamwork (p=0.523) and the dimensions of organizational learning-continuous improvement (p=0.249) were not related to the maturity of patient safety culture. These results highlight the need for hospital management to improve its personnel system and create a complaint system for staff reporting incidents where the parties involved can maintain confidentiality but remain open.